Analysis of the Capital Structure of Small and Medium Enterprises in Particular Industries – the Results of Empirical Research - Kędzior, Dorota (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article analyses the capital structure of small and medium-sized enterprises (SMEs). It presents the basic theories of capital structure relating to SMEs. The empirical verification covered 6727 enterprises from the SME sector for the period 2012–2016 (the article does not discuss micro enterprises). For the purposes of the analysis, the group of enterprises was divided into industries according to the Polish Classification of Activities. SME debt ratios remained at a relatively stable level, with a higher short-term than long-term. Debt ratios in individual industries were highly diversified.